1989
DOI: 10.1073/pnas.86.12.4771
|View full text |Cite
|
Sign up to set email alerts
|

A central nervous system defect in biosynthesis of corticotropin-releasing hormone is associated with susceptibility to streptococcal cell wall-induced arthritis in Lewis rats.

Abstract: We have recently found that susceptibility to streptococcal cell wall (SCW)-induced arthritis in Lewis (LEW/N) rats is due, in part, to defective inflammatory and stress mediator-induced activation of the hypothalamic-pituitary-adrenal (HPA) axis. Conversely, the relative arthritis resistance of histocompatible Fischer (F344/N) rats is related to their intact responses to the same stimuli. Specifically, LEW/N rats, in contrast to F344/N rats, have markedly impaired plasma corticotropin and corticosterone respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
245
2
7

Year Published

1993
1993
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 502 publications
(269 citation statements)
references
References 43 publications
(32 reference statements)
15
245
2
7
Order By: Relevance
“…The findings of this study position the HPA axis, particularly the adrenal glands, centrally in RA pathophysiology. Thus, our findings confirm the central role of the HPA axis in RA as studied in a rat model of arthritis (2).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The findings of this study position the HPA axis, particularly the adrenal glands, centrally in RA pathophysiology. Thus, our findings confirm the central role of the HPA axis in RA as studied in a rat model of arthritis (2).…”
Section: Discussionsupporting
confidence: 85%
“…In an animal model of arthritis, seminal work at the beginning of the 1990s has positioned the hypothalamic-pituitary-adrenal (HPA) axis centrally in chronic inflammation (2). However, findings of those studies have never been confirmed in patients with RA.…”
mentioning
confidence: 99%
“…Lewis rats are highly susceptible to SCW arthritis and other autoimmune models, whereas Fischer rats are resistant. Investigation of the neuroendocrine reactivity in these two strains of rats demonstrated that the reactivity of the hypothalamo-pituitary-adrenal axis in Lewis rats is lower than in Fischer rats (Sternberg, Young, Bernardini, Calogero, Chrousos, Gold, & Wilder, 1989b;Sternberg et al, 1989a). These differences in reactivity were observed after activation of the HPA axis by immune stimuli, e.g., injection with SCW or LPS, as well as after exposure to a novel environment (Sternberg et al, 1989a).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies suggest that other consequences of CRH deficiency are possible. For example, impaired synthesis and secretion of CRH in the paraventricular nucleus of the hypothalamus of the Lewis (LEW/N) rat leads to an increased susceptibility to streptococcal cell wall-induced arthritis (Sternberg et al 1989). The expression of CRH in multiple regions of the mouse brain and in some peripheral tissues beginning at embryonic day 13.5 suggests that CRH expression may also play an important role in development (C. Keegan, unpublished data).…”
mentioning
confidence: 99%